214 CARE OF THE LGBT OLDER ADULT: A NARRATIVE REVIEW. (18th November 2021) - O'Malley, K; Waters, R
Abstract: Background: The number of older Irish adults who identify as Lesbian Gay Bisexual or Transgender (LGBT) is growing. Various barriers exist which can deter LGBT older adults from effectively engaging with healthcare services. These include, and are perpetuated by, heteronormative (and cis-normative) culture within the healthcare setting, and inadequate physician knowledge of LGBT healthcare needs. Methods: The aim of this research is to enhance our awareness and understanding of the challenges experienced by LGBT adults in later life. Key electronic databases were interrogated using a considered search strategy and selected based on specific inclusion criteria. Results: Key themes which emerged were; health disparities of LGBT older adults compared with the wider non-LGBT population; the impact of minority stress on the burden of chronic disease; the role of marginalisation/discrimination as a barrier to engagement with health services; institutional erasure of sexuality, particularly in the setting of long term care; the importance of non-biological chosen family, particularly in the context of advance care planning and preparation for end of life; heteronormativity, cis-normativity and physician bias in the healthcare setting. Conclusion: It is imperative for physicians and allied health professionals to familiarise themselves with the many barriers faced by LGBT older adults when interacting with healthcare services, as well as their unique concerns in later life. In doing so, we can ensure the provision of inclusive and culturally-competent care for all LGBT older adults in Ireland, enabling them to age well in a health system that is sensitive to their needs.